PENGARUH KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. J.CO DONUTS & COFFEE MIKO MALL BANDUNG - Wijaya, Silvi Anggraeni (2014)
Low productivity is indicated by the productivity it self is not reaching the target. In other words, the target can not be realized. There are a number of factors that can affect employee productivity PT JCO Donuts & Coffee Bandung Miko Mall, one of which is compensation. This study aims to describe the system of compensation and productivity PT JCO Donuts & Coffee Bandung Miko Mall. Aspects examined in this study include two things: compensation and productivity. This study used a descriptive and verification methods, the research method used is explanatory survey. Population of fifty respondents. The analysis technique used is the Pearson Product Moment Correlation Coefficient and Simple Regression Analysis. Hypothesis testing using t-test to see the effect by partially. The results showed that compensation and employee productivity PT JCO Donuts & Coffee Bandung Miko Mall in middle/average category. The results of the correlation calculations, variable compensation (X) with variable productivity (Y) has a correlation value of zero point six hundred, it means the compensation variable has a positive relationship with the average classification. The calculation result of simple regression analysis and R Square of zero point three hundred and sixty or thirty- six percent. it means that for thirty- six percent productivity PT JCO Donuts & Coffee Bandung Mall Miko influenced by compensation. While the remaining sixty- four percent are influenced by other factors not examined.